Physical Effects of Maternal Deaths on Midwives' Health: A Qualitative Approach - Anita Fafa Dartey; Ellemes Phuma-Ngaiyaye (Hindawi Limited, 2020)
Grief does not only affect human emotions but also impacts their physical health. Understanding physical grief of people can bring to bear the grip of its daunting nature, a situation where routines become challenging. A qualitative explorative descriptive research method was used. A purposive sample of 18 ward supervisors and 39 ward midwives was used to ascertain the physical effects of maternal deaths on these caregivers in the Ashanti Region of Ghana. Data were collected through semistructured and focus group discussions. Data analysis was done parallel with data collection till saturation was reached. Ethics was obtained from the University of the Western Cape, South Africa, and Ghana Health Service. The findings indicated that generally, as a result of grieving over the deaths of their patients, midwives experienced physical health sufferings. Therefore, reported depression is expressed as insomnia, appetite loss, exhaustion, and social isolation. There is the need to reduce the physical effects of patients' death on caregivers in Ghana and therefore, the study recommends that all hospitals in Ghana utilize employee assistance programmes, a workplace intervention programme designed for such purposes.